The influence of surface treatment on the implant roughness pattern (Journal of Applied Oral Science, 2012)
An important parameter for the clinical success of dental implants is the formation of direct contact between the implant and surrounding bone, whose quality is directly influenced by the implant surface roughness. A screw-shaped design and a surface with an average roughness of Sa of 1-2 µm showed a better result. The combination of blasting and etching has been a commonly used surface treatment technique. The versatility of this type of treatment allows for a wide variation in the procedures in order to obtain the desired roughness. OBJECTIVES: To compare the roughness values and morphological characteristics of 04 brands of implants, using the same type of surface treatment. In addition, to compare the results among brands, in order to assess whether the type of treatment determines the values and the characteristics of implant surface roughness. MATERIAL AND METHODS: Three implants were purchased directly from each selected company in the market, i.e., 03 Brazilian companies (Biomet 3i of Brazil, Neodent and Titaniumfix) and 01 Korean company (Oneplant). The quantitative or numerical characterization of the roughness was performed using an interferometer. The qualitative analysis of the surface topography obtained with the treatment was analyzed using scanning electron microscopy images. RESULTS: The evaluated implants showed a significant variation in roughness values: Sa for Oneplant was 1.01 µm; Titaniumfix reached 0.90 µm; implants from Neodent 0.67 µm, and Biomet 3i of Brazil 0.53 µm. Moreover, the SEM images showed very different patterns for the surfaces examined. CONCCLUSIONS: The surface treatment alone is not able to determine the roughness values and characteristics.